2016
DOI: 10.1097/scs.0000000000002524
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Effect of Autologus Platelet-Rich Fibrin to Barrier Membrane in the Treatment of Periodontal Intrabony Defects

Abstract: The adjunctive use of PRF in combination with barrier membrane is more effective in the treatment of intrabony defects in chronic periodontitis as compared with barrier membrane alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
6

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 52 publications
1
36
0
6
Order By: Relevance
“…The additional use of PRF with bone grafts and collagen membranes has been demonstrated to increase PD reductions and CAL gain and enhance the periodontal regeneration of intrabony defects. 34,35 Moreover, it should be kept in mind that bone healing in intrabony periodontal defects is different from that of PBD due in particular to the differences in blood supply of the periodontium during the healing period. A randomized, controlled, clinical trial evaluated the effect of PRF combined with flap surgery for the treatment of peri-implant bone loss and concluded that the additional use of PRF provided significant improvements in CAL gain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The additional use of PRF with bone grafts and collagen membranes has been demonstrated to increase PD reductions and CAL gain and enhance the periodontal regeneration of intrabony defects. 34,35 Moreover, it should be kept in mind that bone healing in intrabony periodontal defects is different from that of PBD due in particular to the differences in blood supply of the periodontium during the healing period. A randomized, controlled, clinical trial evaluated the effect of PRF combined with flap surgery for the treatment of peri-implant bone loss and concluded that the additional use of PRF provided significant improvements in CAL gain.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Kim et al20 reported that PRF and CGF showed similar new bone formation in rabbit-skull defect healing. The additional use of PRF with bone grafts and collagen membranes has been demonstrated to increase PD reductions and CAL gain and enhance the periodontal regeneration of intrabony defects 34,35. The additional use of PRF with bone grafts and collagen membranes has been demonstrated to increase PD reductions and CAL gain and enhance the periodontal regeneration of intrabony defects 34,35.…”
mentioning
confidence: 99%
“…Seven RCTs addressing the prospective application of PRFs periodontal therapy IBD have been found. Articles that have been found allowed for the following comparisons: (a) PRF/open flap surgery versus open flap surgery [9,10,11]; (b) PRF/Bio-Oss ® constructs (Bio-Oss ® , Geistlich Pharma North America, Inc., Princeton, NJ, USA) versus PRF [12] and (c) PRF/DFDBA constructs versus DFDBA (demineralized freeze-dried bone allograft) [13] (d) PRF/inorganic bovine bone mineral (ABBM) versus ABBM alone [14] and (e) resorbable collagen membrane + PRF versus guidance tissue regeneration [15]. All of the patients who were included in those studies were periodontally stable and systemically healthy individuals who presented: a similar bilateral IBD of at least 5-mm probing depth located in vital asymptomatic teeth with no furcation involvement.…”
Section: Resultsmentioning
confidence: 99%
“…A partir de lo observado por Panda y col. (2016) se constató una mejoría en todos los indicadores evaluados (clínicos y radiográficos) del grupo test, L-PRF + RTG vs. RTG sola. En el caso de la reducción del DIO, la diferencia alcanzó 1,3mm entre ambos grupos, lográndose además un porcentaje de relleno ampliamente superior con L-PRF + RTG (15) .…”
Section: Resultsunclassified